2008
DOI: 10.1002/polb.21460
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling simulation and experimental measurements to characterize chitosan and poly(vinyl pyrrolidone) blend interactions

Abstract: Blends of chitosan and poly(vinyl pyrrolidone) (PVP) have a high potential for use in various biomedical applications and in advanced drug‐delivery systems. Recently, the physical and chemical properties of these blends have been extensively characterized. However, the molecular interaction between these two polymers is not fully understood. In this study, the intermolecular interaction between chitosan and PVP was experimentally investigated using 13C cross‐polarization magic angle‐spinning nuclear magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…To investigate the effect of initial drug concentration on the loading efficiency of the drug, understanding the interactions between the components of the studied system is essential. Previous simulation studies indicated that condensed-phase optimized molecular potentials for atomistic simulation studies (COMPASS) force field effectively and accurately represents the molecular interactions [31][32][33]. Therefore, in this work the COMPASS force field was used to represent all the interactions between the polymer, as the carrier, and the drug in the studied drug delivery system.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…To investigate the effect of initial drug concentration on the loading efficiency of the drug, understanding the interactions between the components of the studied system is essential. Previous simulation studies indicated that condensed-phase optimized molecular potentials for atomistic simulation studies (COMPASS) force field effectively and accurately represents the molecular interactions [31][32][33]. Therefore, in this work the COMPASS force field was used to represent all the interactions between the polymer, as the carrier, and the drug in the studied drug delivery system.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…The radial distribution function (RDF) calculations are performed by simulations for polymer blends, composites, polymer solutions to investigate the interaction between the two types of molecules in the system [77,[81][82][83]. For OPD-CB composite sensor, radial distribution function calculation was performed to investigate the selectivity interaction between the OPD molecule and analyte molecule.…”
Section: Radial Distribution Function Calculation To Investigate Intementioning
confidence: 99%
“…Geometries of PES/ PTFE blends were illustrated in Figure 1. Based on the results of MD simulations, the cohesive energy density (CED), solubility parameter (δ), RDF of atoms, and MSD of polymer blends were analyzed [30].…”
Section: Simulationsmentioning
confidence: 99%